Qadhiyah al-Jawaz al-Mubkir Baina Qanun al-Jawaz al-Madani fi Daul al-Muslimin wa al-Nushshus al-Syar'iyyah - Ghazali, Abdul Malik (al-'adalah, 2014)
In spite of Islamic countries, such as Indonesia, has established family laws, but in fact these laws disobeid. Some peoples of moslem society proved this disobedience by approval of doctrine that allowed this marriage. This paper studied furthermore of underage marriage viewing syaria proofs that admits its in comperative with those forbided. This paper also included some explanations of ulama towards these syaria proofs by using some approach methodologies. By these their explanations can be concluded that texts of Koran and Hadith (prophet tradition) can be understood according to context and human needs. So that religion come for raising the justice and maintaining the real human needs.